Fullerene and oxidative stress - M. A. Orlova; T. P. Trofimova; A. P. Orlov; O. A. Shatalov; A. A. Svistunov; Yu. K. Napolov; V. P. Chekhonin (Онкогематология, 2014)
Fullerene derivatives superfamily attracts a serious attention as antiviral and anticancer agents and drug delivery carriers as well. A large number of such fullerene С60 derivatives obtained to date. However, there is an obvious deficit of information about causes and mechanisms of immediately and long-term consequences of their effects in vivo which is a true obstacle on the way leading to their practical medical using. First, this concerns their impact on the proliferation, apoptosis and necrosis regulation. Fullerene nanoparticle functionalization type, their sizes and surface nanopathology are of great importance for further promoting of either cytoprotective or cytotoxic effects. One of the main effects of fullerenes on living systems is the reactive oxygen species (ROS) formation induction. This lecture provides a modern concept analysis regarding fullerenes effects on ROS formation and modulation of proliferation and apoptosis in normal and tumor cells.